2017
DOI: 10.1080/14767058.2017.1365130
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–foetal attachment independently predicts the quality of maternal–infant bonding and post-partum psychopathology

Abstract: The quality of maternal-foetal bonding may independently predict the quality of maternal-infant attachment and post-partum depressive and anxiety symptoms. A comprehensive assessment of maternal risk factors for perinatal psychopathology during pregnancy should include the evaluation of antenatal attachment that could be modifiable by specific interventions promoting the quality of maternal bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 47 publications
4
57
1
Order By: Relevance
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies [76,[78][79][80]85,87,93,96,100,103,109,113] did not observe significant results. Ten papers reported that lower levels of prenatal attachment were associated with higher postnatal depression scores [74,81,95,99,101,105,110,111,116,117]; however, one study [85] did not support the association between these two variables. Four studies analyzed the influence between partner's depressive symptoms and own prenatal attachment [75,87,97,102].…”
Section: Main Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…Condon (1993) defined it as a prenatal emotional bond between parents and their babies. Muller (1993) described prenatal attachment as "a unique and loving bond that develops between a woman and her fetus" (Alan Dikmen & Cankaya, 2018;Busoneraa, Cataudellab, Lampisb, Tommasic, & Zavattinia, 2017;Dereli, 2013;Forte Camarneiro & Rosado de Miranda Justo, 2017;Göbela et al, 2018;Muller, 1993;Orta & Sümer, 2016;Petri et al, 2018;Tüzün & Sayar, 2006;Yılmaz & Beji, 2010).…”
Section: Introductionmentioning
confidence: 99%